Characterization of Melanoidins and Color Development in Dulce de Leche, a Confectionary Dairy Product With High Sucrose Content: Evaluation of pH Effect, an Essential Manufacturing Process Parameter - Rodríguez, Analía; Lema, Patricia; Bessio, María Inés; Moyna, Guillermo; Olivaro, Cristina; Ferreira, Fernando; Panizzolo, Luis Alberto (Frontiers in Nutrition, 2021)
The effect on color of the initial pH employed in dulce de leche (DL) production was evaluated through physicochemical and spectroscopical characterization of the melanoidins formed in the process. Melanoidins originated at pH values of 6.5, 7.0, and 7.5 were released by enzymatic hydrolysis of the protein backbone and purified by gel filtration. They showed a significant degree of polydispersity, in general, with MWs below 1,800 Da. DL produced at higher pH released melanoidins with higher average MW after the enzymatic hydrolysis. They also presented darker colors (dE*ab, C*), more closely resembling those typical of the commercial product. Analysis of the fractions isolated by gel filtration using HPLC-DAD and multinuclear NMR showed an heterogeneous and complex composition. Even though structurally related, the 1H NMR spectra of melanoidins showed higher degree of aromaticity at higher pH values. In conclusion, the pH employed in DL production affects the amount and structure of the colored products originated by MR reactions, and thus the color of the final product.